Characterization and identification of ascorbyl methylsilanol pectinate for cosmetic formulations application (Brazilian Journal of Pharmaceutical Sciences, 2022)
The ascorbyl methylsilanol pectinate (AMP) presents the same functional properties of ascorbic acid (AA). Besides antioxidant and depigmentant activity, the AMP presents silanol in its chemical structure. The aim of this work was to characterize and indentify the AMP alone and in cosmetic formulations. The following techniques were employed: Fourier Transform Infrared Spectrophotometry, particle size distributions, in vitro antioxidant activity with 2.2-diphenyl-1 picrylhydrazyl (DPPH) and Oxigen Radical Absorbance Capacity Assay and High Performace Liquid Chromatography (HPLC) (developed and validated method) for the active ingredient; Microscopy, HPLC and Normal Stability Assay (NSA) for the emulsions. Particle size distributions results showed that the average size of AMP was 1.0 µm and polydispersity index was 0.1. In DPPH assay AA and AMP were statistically the same. The value of ORAC obtained for AMP was 0.74 and for AA in the literature was 0.95. In the NSA the formulations were stable in conditions of 5.0 and 45.0 ± 2.0 ºC for 90 days. Adequate stability at ambient temperature out of reach of light was also observed. Thus, this works presented an acceptable method for quantification of AMP alone and in cosmetic formulations. AMP was an adequate choice for the incorporation in emulsions with antioxidant efficacy.